All the Days of Summer : a Novel - Thayer, Nancy 1943- (New York : Ballantine Books, 2023)
"A woman's second act on the beautiful island of Nantucket delivers much more than she expected in this hopeful novel by New York Times bestselling author Nancy Thayer. Heather Willette has a good life in Concord, Massachusetts-complete with a husband who runs his own business and a son to take up his mantle one day. But now that her marriage has fizzled out and Ross, her only child, is graduating from college and getting serious with his girlfriend, Heather wonders if that life is the one she really wants. Ready to seek out her own happiness and discover herself again, Heather decides to leave her husband and rent a cottage on Nantucket. And her plan is going perfectly-until Ross announces he's moving to Nantucket to work at his girlfriend's family's construction business instead of going back home to work with his own father, like he'd promised. Worst of all for Heather, this means having to get along with her. Kailee Essex is thrilled that Ross is willing to move to her hometown. She has big hopes for their happily ever after, especially now that her parents are finally showing interest in her career. She's less thrilled, however, about his mother living nearby. Kailee has clashed with Heather since the day they met. But anything is possible in the summer sun and sea breezes of Nantucket-even reconciliation. And when change comes sooner than either Heather or Kailee expect, they must learn to overcome their differences to fight for the future they want. With All the Days of Summer, beloved storyteller Nancy Thayer delivers a moving novel that explores the complexity of family and the unexpected ways fate can guide you forward"--
Keywords: Domestic fiction; Novels